A Novel Approach for Achieving High‐Efficiency Photoelectrochemical Water Oxidation in InGaN Nanorods Grown on Si System: MXene Nanosheets as Multifunctional Interfacial Modifier. (14th February 2020) - Lin, Jing; Yu, Yuefeng; Zhang, Zhijie; Gao, Fangliang; Liu, Sheng; Wang, Wenliang; Li, Guoqiang
Abstract: MXene nanosheets with attractive electrical conductivity and tunable work function have been adopted as multifunctional interfacial modifier between InGaN nanorods and Si for photoelectrochemical water oxidation for the first time. Compared to bare InGaN/Si systems, MXene interfacial layers give rise to an ultralow onset potential of 75 mV versus reversible hydrogen electrode (RHE), which is the highest ever reported for InGaN‐ or Si‐based photoanodes by interfacial modification. Furthermore, the modified photoanode exhibits a significantly enhanced photocurrent density (7.27 mA cm −2 ) at 1.23 V versus RHE, which is about 10 times higher than that achieved with the InGaN/Si photoanode. The detailed mechanism demonstrates that the formed type‐II band alignment in InGaN/MXene heterojunction and an Ohmic junction at the MXene/Si interface make MXene an ideal electron‐migration channel to enhance charge separation and transfer process. This synergetic effect of MXene can significantly decrease the charge resistance at semiconductor/Si and semiconductor/electrolyte hetero‐interfaces, eventually resulting in the fast hole injection efficiency of 82% and superior stability against photocorrosion. This work not only provides valuable guidance for designing high‐efficiency photoelectrodes through the integration of multiscale and multifunctional materials, but also presents a novel strategy for achieving high‐performance artificial photosynthesis by introducing interfacial modifier. Abstract : An InGaN/MXene hetero‐structured photoanode with highly conductive MXene (≈117.06 mΩ) is developed as a multifunctional interfacial modifier for InGaN nanorods and Si substrates using a molecular beam epitaxy system. This approach presents a valuable avenue for achieving high‐efficiency artificial photosynthesis through the integration of multiscale and multifunctional materials.